Insulin‐like growth factor 1 prevents diastolic and systolic dysfunction associated with cardiomyopathy and preserves adrenergic sensitivity. (8th October 2015) - Roof, S. R.; Boslett, J.; Russell, D.; del Rio, C.; Alecusan, J.; Zweier, J. L.; Ziolo, M. T.; Hamlin, R.; Mohler, P. J.; Curran, J.
Abstract: Aims: Insulin‐like growth factor 1 (IGF‐1)‐dependent signalling promotes exercise‐induced physiological cardiac hypertrophy. However, the in vivo therapeutic potential of IGF‐1 for heart disease is not well established. Here, we test the potential therapeutic benefits of IGF‐1 on cardiac function using an in vivo model of chronic catecholamine‐induced cardiomyopathy. Methods: Rats were perfused with isoproterenol via osmotic pump (1 mg kg −1 per day) and treated with 2 mg kg −1 IGF‐1 (2 mg kg −1 per day, 6 days a week) for 2 or 4 weeks. Echocardiography, ECG, and blood pressure were assessed. In vivo pressure–volume loop studies were conducted at 4 weeks. Heart sections were analysed for fibrosis and apoptosis, and relevant biochemical signalling cascades were assessed. Results: After 4 weeks, diastolic function (EDPVR, EDP, tau, E/A ratio), systolic function (PRSW, ESPVR, dP/dtmax) and structural remodelling (LV chamber diameter, wall thickness) were all adversely affected in isoproterenol‐treated rats. All these detrimental effects were attenuated in rats treated with Iso+IGF‐1. Isoproterenol‐dependent effects on BP were attenuated by IGF‐1 treatment. Adrenergic sensitivity was blunted in isoproterenol‐treated rats but was preserved by IGF‐1 treatment. Immunoblots indicate that cardioprotective p110 α signalling and activated Akt are selectively upregulated in Iso+IGF‐1‐treated hearts. Expression of iNOS was significantly increased in both the Iso and Iso+IGF‐1 groups; however, tetrahydrobiopterin (BH4) levels were decreased in the Iso group and maintained by IGF‐1 treatment. Conclusion: IGF‐1 treatment attenuates diastolic and systolic dysfunction associated with chronic catecholamine‐induced cardiomyopathy while preserving adrenergic sensitivity and promoting BH4 production. These data support the potential use of IGF‐1 therapy for clinical applications for cardiomyopathies.